2011
DOI: 10.1017/cbo9781139013345
|View full text |Cite
|
Sign up to set email alerts
|

Political Transformations and Public Finances

Abstract: How did today's rich states first establish modern fiscal systems? To answer this question, Political Transformations and Public Finances by Mark Dincecco examines the evolution of political regimes and public finances in Europe over the long term. The book argues that the emergence of efficient fiscal institutions was the result of two fundamental political transformations that resolved long-standing problems of fiscal fragmentation and absolutism. States gained tax force through fiscal centralization and res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
82
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 195 publications
(84 citation statements)
references
References 0 publications
1
82
0
1
Order By: Relevance
“…The existing literature offers two hypotheses for China's low tax revenue in general: the absence of warfare and the ideology of benevolence. Economic historians have shown that warfare was a major driver for European states to expand fiscal capacity (Hoffman and Rosenthal 1997;O'Brien 2005;Dincecco et al 2011;Gennaioli and Voth 2011). In this view, the absence of interstate competition in China and the resulting low fiscal demand were the primary reasons for low taxation in China (Rosenthal and Wong 2011).…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…The existing literature offers two hypotheses for China's low tax revenue in general: the absence of warfare and the ideology of benevolence. Economic historians have shown that warfare was a major driver for European states to expand fiscal capacity (Hoffman and Rosenthal 1997;O'Brien 2005;Dincecco et al 2011;Gennaioli and Voth 2011). In this view, the absence of interstate competition in China and the resulting low fiscal demand were the primary reasons for low taxation in China (Rosenthal and Wong 2011).…”
Section: Figmentioning
confidence: 99%
“…9 To our knowledge, this study is the first comparative analysis of state capacity in preindustrial Asia. 10 The European experience indicates that most states had a strong fiscal system in place before industrializing (Dincecco 2011;Johnson and Koyama 2014a, b). Indeed, there is a growing body of theoretical and empirical research highlighting the importance of state capacity in facilitating modern economic growth (Acemoglu 2005;Persson 2009, 2013;Dincecco and Prado 2012;Dincecco and Katz 2014).…”
Section: Figmentioning
confidence: 99%
“…Yet, it is clear that secrecy makes it more difficult to trade votes. 6 possibility recently pursued by Besley and Persson (2011) and by Dincecco (2009Dincecco ( , 2011 and tested in Dincecco and Prado (2012) is that wars foster state capacity building, in particular in terms of improved tax collection technologies. Once the need for war-finance is over, the capacity to raise more revenue persists and may, if there is demand for public services and redistribution, lead to a permanent fiscal expansion.…”
Section: Hypothesesmentioning
confidence: 99%
“…These variables are constructed by Dincecco (2011) from a large number of primary and secondary sources. They measure total revenue and total expenditure of the central government in each country per capita in gold grams.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation